2020
DOI: 10.1111/rda.13786
|View full text |Cite
|
Sign up to set email alerts
|

Mitoepigenetics: Methylation of mitochondrial DNA is strand‐biased in bovine oocytes and embryos

Abstract: Global mitochondrial DNA (mtDNA) methylation has been recently described in bovine and showed particular signatures in both gametes and embryos. Here, we investigated the distribution of mtDNA methylation through strand-specific mapping of methylation sites to gain perspective on how epigenetic mechanisms can be involved in mitochondrial function. We demonstrate that in both oocytes and How to cite this article: de Lima CB, Sirard M-A. Mitoepigenetics: Methylation of mitochondrial DNA is strand-biased in bovin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Besides, the profile of methylated residues was associated to the origins of the oocyte (high-quality OPU-derived oocytes versus abattoir-derived oocytes) and was inversely correlated with differences in the expression of specific mitochondrial genes [ 21 ]. Furthermore, as observed in other studies, methylation was strand-biased and not restricted to CG context [ 22 ].…”
Section: Introductionsupporting
confidence: 76%
“…Besides, the profile of methylated residues was associated to the origins of the oocyte (high-quality OPU-derived oocytes versus abattoir-derived oocytes) and was inversely correlated with differences in the expression of specific mitochondrial genes [ 21 ]. Furthermore, as observed in other studies, methylation was strand-biased and not restricted to CG context [ 22 ].…”
Section: Introductionsupporting
confidence: 76%
“…However, some differences between mtDNA and nuclear DNA methylation exist. Indeed, contrarily to genomic DNA, mtDNA showed to possess high levels of non-CpG versus CpG methylation, which is not symmetrical on both strands, being biased toward the L-strand, and it seems that depending on the cell type and context of cytosine methylation, mtDNA methylation can play a role in the regulation of mtDNA gene expression or mtDNA replication [ 46 , 50 , 54 , 60 , 61 , 62 ]. Additionally, 5-hmC has been detected in mtDNA, and there is evidence that 5-hmC marks are dynamic in nature and are enriched in the upstream of gene start site regions and in the gene body, similarly to nuclear genes [ 63 ].…”
Section: Mitoepigeneticsmentioning
confidence: 99%
“…We suggested that mtDNA methylation could be inherited from oocytes to early embryos since mtDNA methylation patterns were more conserved between oocytes and blastocysts than granulosa cells. Another recently published article from our team also indicated that the 5mC frequency is biased and not symmetrically distributed on both strands of bovine mitochondrial DNA in oocytes and embryos ( de Lima & Sirard, 2020 ). Mitochondrial DNA methylation may also respond to different environmental stressors such as metals, smoking, food supplements, drugs, and pollutants ( Sharma et al, 2019 ).…”
Section: Introductionmentioning
confidence: 79%